Interpersonal Communication Training To Reduce Student Aggressiveness - Eka Aryani; Abdul Hadi; Moh. Khoerul Anwar; Anifa Tuzzuhroh Nurbaiti (International Journal Of Community Service, 2024)
Aggression is a behavioral problem that often occurs in students. Aggression can be caused by various factors, one of which is a lack of interpersonal communication skills. Excessive aggressive behavior can have a negative impact on students and their environment. Aggressive students can experience problems in learning, socializing and establishing relationships with other people. Aggressive behavior can also cause problems in the school environment, such as brawls, bullying and sexual violence. Interpersonal communication training is one effort that can be made to reduce aggression in students. Students who need to reduce aggression are students who have excessive aggressive behavior or often carry out aggressive behavior. This study aims to test the effectiveness of interpersonal communication training in reducing aggression in students. The research results show that interpersonal communication training can reduce aggression in students. Students who took part in interpersonal communication training showed a significant reduction in aggression scores compared to students who did not take part in the training.